Development and piloting of Maize Nutrient Manager mobile decision support tool - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
In two growing seasons, a successful pilot was run: 46 extension officers used the app to collect field-level management data, and advice more than 3,000 smallholder maize growers on their nutrient and associated crop management. The app targets smaller yield gaps, high N use efficiency and low GHG emissions.